Intergenerational Transmission of Child Abuse and Neglect: A Transdisciplinary Analysis. (19th February 2019) - Van Wert, Melissa; Anreiter, Ina; Fallon, Barbara A.; Sokolowski, Marla B.
Parents who experienced maltreatment in childhood may be at an increased risk of presenting abusive or neglectful behavior toward their own children. Research suggests reoccurring patterns of abuse and neglect across generations, but the factors that influence these behavioral patterns are complex and poorly understood. Although abusive or neglectful parenting styles undoubtedly are strongly influenced by social factors (ie, "nurture"), there might be underlying biological components to perpetuating behavioral patterns (ie, "nature"). Importantly, nature and nurture are known to interact in shaping developmental outcomes, and as such should not be considered in isolation. In this review, we examine the evidence regarding the inheritance of abusive and/or neglectful parenting behavior using a transdisciplinary approach. We integrate knowledge of the social and biological science fields on the continuance of abusive and neglectful behavior, as well as the methodological challenges that complicate the interpretation of existing research. Finally, we stress the importance of considering contextual factors of both social and biological research findings concerning the intergenerational inheritance of child abuse and neglect and discuss the potential for early social intervention to disrupt harmful intergenerational patterns.